Bidirectional Dynamics between Hyperglycemia and Periodontal Infections - K. Swapna Kumari1 , Shashirekha G.2 , Suchanda Dey3 , E. Subudhi4 , Rini Behera5 , Siba Prasad Jena5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Hyperglycemia induces a higher rate of activation pathways responsible for inflammation which leads tomicrovascular and macrovascular complications, oxidative stress as well as apoptosis. In the pathologicalmanifestation of hyperglycemic events, a raised level of inflammatory markers such as: IL6, TNF-?and C-reactive protein occurs which in turn promotes acute-phase of inflammation leading to signalingimpairment of insulin function and insulin resistance. On the other hand, enhanced systemic inflammationdue to periodontal diseases mediated by the release of IL-6 and TNF-? happens when associated withhyperglycemia. This review article deals with assessment on hyperglycemia and its correlation to dentalpathologies with special reference to periodontitis and vice versa. Studies show that the paradigm shift in theoral microbiota due to hyperglycemic condition resulting in the increase in the pathogenicity of associatedpathogenic microbes which results in increased inflammation and bone loss in periodontal pathologies.The extensive studies about the association between inflammatory periodontal disease and diabetes show thecyclic relationship between the two. Diabetes predisposes the individual to periodontal infections and alsothe later exacerbates or worsens the glycemic control in diabetic patients. Routine periodontal examinationprovides an insight for the early diagnosis of diabetes in undiagnosed patients and may reduce the worseningof metabolic control thereby preventing serious complications. Also the oral health of diabetic patients maybe improved and well maintained with proper management of blood glucose levels.Although there are evidences in literature to establish correlation between Diabetes Mellitus associatedwith periodontitis and vice versa, still the outcomes are not conclusive. Therefore large-scale prospectiveepidemiological analysis are the only sought after approach to clearly bring in the connectivity betweenDiabetes and Periodontal disease